The Taliban at war: 2001-2018 - Giustozzi, Antonio (Oxford scholarship online Political Science, 2019)
How does the Taliban wage war? How has its war changed over time? Firstly, the movement's extraordinary military operation relies on financial backing. This volume analyses such funding.